Breeding potatoes for resistance to bacterial blight in Brazil: a quick review in face of a more effective screening protocol. - LOPES, C. A. (2018)
Bacterial wilt (BW), caused by Ralstonia solanacearum, is one of the most important diseases of potato (Solanum tuberosum subsp. tuberosum) in Brazil and the main cause of rejection of fields for tuber seed certification. Genetic resistance is not a feasible control currently since no commercially-appealing BW resistant cultivars are available... After many years of germplasm breeding, we succeeded in developing two resistant clones, MB- 03 and MB9846-01, both producing tubers with rather reasonable characteristics.